Load balancer system for an intrusion prevention system - Pantola, Alexis V. (Animo Repository, 2006)
Network access has been an essential resource in most businesses. This allows expensive supplies such as electronic storage and printers to be shared among users through network connection. It also allows information that is inaccessible before to be available through the internet. However, hackers have taken advantage of this technology to illegally gain access to the resources of many organizations. This resulted to network engineers developing network security devices like intrusion prevention system (IPS). IPS is a vast improvement from its predecessor the firewall. Unlike the firewall, IPS inspects the actual data of a network packet ensuring that it does not contain a malicious content. This malicious content may cause irreversible damage to information stored in a network system. However, since IPS performs extensive inspection of network packets, it generally causes delay when enormous number of packets is present in the network. This side effect is considered unacceptable to most network administrators. One of the remedies to this problem is to use multiple IPS such that the work of inspecting network packets is distributed. This solution requires the use of a load balancer. This paper discusses a load balancer system (LBS) that is used to distribute the work to several IPS. Implementation issues such as the integration of a port scan detector inside the LBS are also explained. Experiments on the systems show that the load of three IPS are distributed evenly. Each IPS has 66.6% load reduction when used together with the LBS.